1997
DOI: 10.1128/aem.63.6.2232-2239.1997
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and functional analysis of styrene catabolism genes from Pseudomonas fluorescens ST

Abstract: The nucleotide sequence of the 4,377-bp chromosomal region of Pseudomonas fluorescens ST that codes for the oxidation of styrene to phenylacetic acid was determined. Four open reading frames, named styA, styB, styC, and styD, were identified in this region. Sequence analysis and biotransformation assays, performed with batch and continuous cultures, allowed us to identify the functions of the sequenced genes. styA and styB encode a styrene monooxygenase responsible for the transformation of styrene to epoxysty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 48 publications
4
63
0
2
Order By: Relevance
“…Considering the genomic potential and the substrate spectrum a degradation pathway for 2,4-TDA with candidate genes encoding the enzymes involved can be suggested (Figure 3). Although also a monooxygenation of an aromatic ring lacking hydroxyl groups has been reported in the case of styrene (Beltrametti et al, 1997), an initiation of the degradation of not yet activated aromatics by flavin monooxygenases is rather unlikely (Van Berkel et al, 2006). In contrast to that, hydroxylation of substituents at the aromatic ring, like the methyl group of toluene, is common (Assinder and Williams, FIGURE 3 | Proposed degradation pathway including extradiol cleavage of 4-aminocatechol for 2,4-TDA in the putative Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the genomic potential and the substrate spectrum a degradation pathway for 2,4-TDA with candidate genes encoding the enzymes involved can be suggested (Figure 3). Although also a monooxygenation of an aromatic ring lacking hydroxyl groups has been reported in the case of styrene (Beltrametti et al, 1997), an initiation of the degradation of not yet activated aromatics by flavin monooxygenases is rather unlikely (Van Berkel et al, 2006). In contrast to that, hydroxylation of substituents at the aromatic ring, like the methyl group of toluene, is common (Assinder and Williams, FIGURE 3 | Proposed degradation pathway including extradiol cleavage of 4-aminocatechol for 2,4-TDA in the putative Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…2b) suggests that biosurfactant production might be highly regulated or that insertion sequences abolish its production. IS21-like insertion sequences affecting expression of specific genes are found in P. fluorescens isolates (Solinas et al, 1995;Beltrametti et al, 1997). Clearly, the 7·1-kb DNA fragment complementing the biosurfactant activity awaits nucleotide sequencing and translational analyses, from which the open reading frame encoding the type of surfactant produced could be identified and insights into the genetic organization with regard to the regulation of the locus could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Airborne emissions of styrene, even at low concentrations, often cause a problem because of their malodorous character and their toxic and carcinogenic effects (42). The removal of styrene from industrial waste gases could be accomplished by using styrene-degrading bacteria as biocatalysts; however, little is known concerning the microbial metabolism of styrene (6,42). Two main routes of aerobic styrene breakdown have been described: (i) oxidation of the vinyl side chain with the formation of phenylacetate and (ii) initial oxidation of the aromatic nucleus (42).…”
mentioning
confidence: 99%
“…The only information about the organization of the styrene catabolic genes has been recently obtained for Pseudomonas fluorescens ST (6,25). This strain degrades styrene by oxidation of its lateral chain, and it has been shown that the upper pathway for the conversion of styrene to phenylacetate is encoded by four catabolic genes, styABCD (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation